Robust and reliable control of linear singularly perturbed systems - Li, Yan. (2008)
This thesis presents the research work on robust and reliable control for singularly perturbed systems. It consists of two parts. The first part is concerned with Riccati equation approach. The second part is concerned with LMI approach.